Workout Monitoring Robot: A Robotic Approach for Real-Time Workout Monitoring and Guidance - Walke, Shreyas; Wadekar, Yash; Ladawa, Aditya; Khopade, Pratik; Pandit, Shraddha V (International Journal of Computer Sciences and Engineering, 2024)
In this research paper, we present the development and implementation of a cutting-edge Workout Monitoring Robot designed to monitor and guide user’s exercises with its capability of pose estimation and correction and natural language interactions that revolutionize the way individuals engage in exercise routines. Whereas the current research that part-take in similar activities have had much difficulty in flexibility and ease of interaction. This study focuses on enhancing the effectiveness and safety of physical fitness activities by imposing advanced technologies including human pose estimation, autonomous robot navigation and a sophisticated human-computer interface driven by NLP. This research attempts to open the door to a new era of smart and responsive workout assistance, ultimately improving health and well-being.